Domestic Sexual Violence and Sexual Problems Among Gynecology Outpatients: An Example from Turkey - YILDIZ, HATİCE (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2014)
Domestic violence is a universal problem, and sexual violence in marriage, in particular, is a hidden form of it. This descriptive, cross-sectional study was conducted to determine to the prevalence of domestic sexual violence by husbands, the prevalence of sexual problems, and the relation of these among married women attending a gynecology outpatient clinic. This study was performed in a university hospital in Turkey and data were collected February-April 2009. The study sample consisted of 200 married women, 53% of whom reported having been exposed to at least one type of domestic sexual violence behaviors by their husbands. Among those behaviors, the rate of marital rape was 33%. The frequency of experiencing any sexual problem was 82%. Women expressed that they mostly had orgasmic problems, and their husbands had premature ejaculation problems. The majority of women who reported sexual violence reported experiencing sexual problems; the frequency of sexual problems was higher in the participants who did (94.3%) than in those who did not report (68.1%) sexual violence (p < .001). Bad sexual harmony (Odds ratio [OR] = 13.50, 95% confidence interval [CI] = 3.87-47.01) and experiencing sexual problems (OR = 12.67, 95% CI = 3.78-42.35) were strongly related to sexual violence in marriage. The results also revealed that the prevalence of sexual violence and sexual problems among those married women who attended gynecology clinics was considerable, even though they did not report this to the health care provider as a problem.
Keywords: sexual abuse; sexual violence; marital rape; sexual problem; gynecology clinics; WOMEN; HEALTH; SATISFACTION; ABUSE